Dampak Penerapan PSAK 72 Terhadap Pengakuan Pendapatan di Sektor Konstruksi: Studi Tinjauan Literatur - Dika Yulistini; Kristom Eko Kanika; Muhammad Fikri Ramadhan; Rinny Meidiyustiani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to identify findings from a literature review related to revenue recognition based on PSAK 72 in construction companies. Using a literature review method of 13 articles taken from Connected Papers, this research finds that PSAK 72, which is an adoption of IFRS 15, introduces significant changes in the way construction companies report income. Through a five-step model (contract identification, performance obligations, transaction price, price allocation, and revenue recognition), PSAK 72 provides greater transparency. Construction companies apply input (cost-to-cost) and output (milestone) methods to reflect project progress. Although it provides benefits in the form of reporting accuracy, PSAK 72 also presents challenges such as cost estimates, contract changes, and additional disclosures. This standard is expected to increase stakeholder confidence and provide a more realistic picture of the financial performance of construction companies.